Does brown trout (Salmo trutta L.) larval development retardation caused by short-term exposure to low pH and elevated aluminum concentration affect a second episode of toxicity? - Çalta, M (Blackwell Verlag Gmbh, 2002)
This study examines whether brown trout larval development retardation caused by an early episode of low pH and elevated aluminum toxicity affects the outcome of a later toxicity episode. Yolk-sac brown trout, Salmo trutta L., were exposed to four different patterns of low pH (4.5) and aluminum (12 mol L-1 ) episodes. A continuous control (pH 5.6 and zero aluminum) was also provided. Mortality in the control fish was 5.0%. The highest mortality (91.6%) occurred in S. trutta subjected to two later episodes (treatment 2) which were temporally very close together. Mortality declined (30%) as the interval between the two episodes (treatment 3) was increased. The lowest mortality (16.7%) occurred when the duration of the early episode was doubled (treatment 4). Mortality in animals exposed to only a single episode (treatment 1) at the late yolk-sac stage was rather higher (51.6%) when compared with mortalities in animals exposed to double episodes, the first of which being in the early yolk-sac stage (treatments 3 and 4). Mortality was found to be very significant both among treatments (two-way analysis of variance (anova), df=4, F -value=3.01, P<0.05) and time periods (two-way anova, df=5, F -value=4.84, P<0.01). In all treatments, gross development, net uptake of minerals (except Mg) and calcium deposition in the skeleton was impaired. The advantages and disadvantages of larval development retardation in the early yolk-sac stage is discussed.
Keywords: Yolk-Sac Fry; Skeletal Calcium Deposition; Juvenile Rainbow-Trout; Brook Trout; Salvelinus-Fontinalis; Acid Water; Mineral Uptake; Ion Balance; Soft-Water; Survival